Solitary Colorectal Cancer Metastasis to the Pancreas. (7th November 2019) - Karageorgou, M.; Myoteri, D.; Kotsis, T.; Polymeneas, G.; Bournakis, E.; Dellaportas, D.
Abstract : Introduction. Secondary pancreatic metastasis from other solid organ malignancy is rare and accounts for less than 2% of all pancreatic tumors. The aim of this study is to highlight that colorectal metastatic disease in the pancreas could be in selected cases an indication for surgery rather than for palliative chemotherapy. Case Presentation . We present a case of a 62-year-old Caucasian female with a history of rectal adenocarcinoma. Four years ago, the patient underwent low anterior resection of the rectosigmoid, post neoadjuvant chemoradiotherapy, with adjuvant chemotherapy. During her follow-up, imaging examinations revealed a lesion in the pancreatic neck with features indicating primary pancreatic cancer. Near-total distal pancreatectomy with en bloc splenectomy was performed. Histopathology revealed metastatic disease compatible with colorectal adenocarcinoma as the primary cancer. Second-line chemotherapy was decided from the institutional tumor board. The patient remains disease free one year later. Conclusion. Pancreatic lesions in patients with a history of extrapancreatic malignancy should raise suspicions of metastatic disease. Surgical intervention is a legitimate treatment option for these pancreatic lesions, since they represent solitary disease deposits and of course in the context of multidisciplinary meeting decisions, and after proper and extensive staging investigations.